Role of gratitude and obligation in long term customer relationships. (July 2016) - Dewani, Prem Prakash; Sinha, Piyush Kumar; Mathur, Sameer
Abstract: This paper examines the role of gratitude and obligation in customer relationships. We surveyed 398 customers exiting grocery and clothing stores in Ahmedabad and Jaipur cities in India, after they had finished shopping. We analysed their responses using structural equation modelling (SEM). We found that social and structural investments by sellers created gratitude among customers, resulting in short-term purchase intensions and increased customer loyalty. In contrast, financial investments made by sellers created obligation among customers, and reduced customer loyalty. The paper also discusses theoretical and managerial implications of these findings. Highlights: We examine role of gratitude and obligation in long-term customer relationships. We classify RM investments as per the feelings they trigger i.e. positive or negative. Social and structural investments lead to gratitude which in turn leads to loyalty. In contrasts, financial investments lead to obligation in-turn negative loyalty.